Integrative taxonomic revision of the genus Phaselia Guenée, [1858] (Geometridae: Ennominae) in the Middle East and Central Asia - Werner, Maria Johanna; Hausmann, Axel; Kostjuk, Igor; Wanke, Dominic; Rajaei, Hossein (Zootaxa, 2023)
In the past, the high intraspecific variation of wing pattern within the genus Phaselia Guenée, [1858] repeatedly led to misidentifications. In this study, we applied an integrative approach using external and internal morphological characters, along with DNA barcoding and distribution data to review the taxonomy of the genus Phaselia in the Middle East and Central Asia. For this study, 710 specimens, including type specimens and 242 genitalia slides were prepared and examined. As a result, P. phaeoleucaria (Lederer, 1855) stat. rev. is reinstated from synonymy of P. serrularia; P. phaeoleucaria shurensis Wehrli 1941 comb. nov. is regarded as a subspecies of P. phaeoleucaria stat. rev. instead of a subspecies of P. serrularia; P. serrularia catharia Wehrli, 1941 syn. nov. is regarded as a junior synonym of P. phaeoleucaria shurensis comb. nov.; P. narynaria Oberthür, 1913 syn. nov. is regarded as a junior synonym of P. serrularia (Eversmann, 1847); P. pithana Wehrli, 1941 bona sp. is raised to species level from subspecies of P. serrularia. Furthermore, two species and two subspecies are described as new to science: P. smettboi sp. nov., P. sihvoneni sp. nov., P. erika jonubi ssp. nov. and P. erika sindhi ssp. nov. Wing pattern, and both male and female genitalia of all discussed taxa are illustrated, their distribution patterns are shown on a map and CO1 data is evaluated to confirm our taxonomic decisions.